Y cell line in a turner mosaic: a case report - Bandyopadhyay, D.; Sharma, A.; Birla, S.; Sharma, A. (Scientific Journal of Medical Science, 2014)
Turner Syndrome is one of the most common chromosomal aneuploidy seen in humans with an incidence of about 1: 2500 newborn females. Approximately 60% patients with Turner syndrome have 45, X karyotype while others show X chromosome abnormalities like deletions of long arm or short arm, isochromosome or ring chromosome. About 6-9% cases also show presence of Y chromosome or Y derived sequences. Turner Syndrome patients with ovarian dysgenesis and Y Cell- line / Y derived sequences have higher risk of developing gonadal tumors. In the present study we report on a patient with Turner Syndrome showing mosaicism with Y cell line. Our case is a 19 yrs old unmarried female who reported to Gyn OPD with primary Amenorrhoea. She was referred to our lab for cytogenetic analysis. Routine karyotype was done using standard protocol for Giemsa trypsin banding. The Cytogenetic results were confirmed by Flourescent In Situ Hybridisation (FISH) using probes for chromosomes X and Y. The patient was a Turner mosaic with karyotype 45, X in 65% and 46, XX in 10% of the cells; the remaining 25% of the cells showed presence of Y- chromosome with karyotype 46, XY. The detection of Y-cell line is important in view of 10-30% higher risk of developing gonadal tumors. Prophylactic gonadectomy is recommended to patients of Turner syndrome with Y-chromosome mosaicism and ovarian dysgenesis.